Evaluation of Hydraulic Conductivity in Upper Krishna Project Command Area of Karnataka - Balakrishnan, P; Shirahatti, M S; Deshpande, Girish B; Barker, R D (Journal of Agricultural Engineering, 2005)
The study area consists of black soils (Vertisols) with high clay content underlain by bedded limestone located in canal seepage affected zone in Upper Krishna Project command area, Karnataka. In situ measurements on grid basis in the Operational Research Project (ORP) area (180 ha) and aerial estimates using q-h relationships of pipe drains in Phase-I area (14.9 ha) of the above project were obtained and compared. The point K-values varied from 0.004 to 0.559 m/d and followed the log normal distribution. The geometric mean (GM) values of K of the ORP and the Phase-I areas were 0.077 and 0.070 m/d respectively. The K-contour map was drawn and the vertical as well as radial K values were also computed. The GM areal K values for the entire strata (Ko) and the layer below the drains only (Kb) ranged from 1.114 to 1.449 m/d and from 1.145 to 1.348 m/d at 90 per cent confidence limits respectively, indicating that the flow below the drain level was pre-dominant. This observation of much larger areal K-values in comparison with the point measurements as explained by higher discharge was in line with the reported literature and also found to have more practical applicability.